DEGRADASI NILAI KEWARGANEGARAAN GENERASI MUDA SEBAGAI TANTANGAN GURU PKN - Indarwati Indarwati; Sulton Sulton (EDUPEDIA, 2026)
The degradation of civic values among the younger generation has become a serious concern and a major challenge for Civic Education (Pendidikan Kewarganegaraan/PKn) in Indonesia. This phenomenon is marked by the declining sense of nationalism, low civic engagement, weakened moral responsibility, and the growing influence of digital culture that often contradicts the foundational values of Pancasila. This study aims to analyze the forms and causes of civic value degradation among youth and to examine the role of Civic Education in addressing this issue. The research focuses on students as the main object of study, using both primary data obtained through observations and interviews, and secondary data derived from relevant literature, journals, and policy documents. A qualitative descriptive method is employed to explore the phenomenon in depth and to interpret social realities related to civic education practices. The findings indicate that the degradation of civic values is influenced by several factors, including the dominance of social media, lack of exemplary role models, ineffective learning methods, and the tendency of Civic Education to emphasize cognitive aspects over affective and behavioral dimensions. As a result, students often perceive PKn as a theoretical subject with limited relevance to real-life civic practices. The study concludes that Civic Education must undergo pedagogical transformation by adopting contextual, participatory, and value-oriented learning approaches. Strengthening character education, integrating digital literacy, and fostering critical and reflective thinking are essential strategies to restore civic values among the younger generation and to reinforce the role of PKn in shaping responsible and democratic citizens.